Nutrition and cancer: modern aspects of a healthy lifestyle (literature review) - O. P. Kolesnik; O. M. Levyk; D. Ye. Cherniavskyi; V. O. Kuzmenko; L. S. Lytvynenko (Zaporozhye State Medical University, 2022)
Despite significant improvements in screening, diagnosis and targeted therapy, cancer remains the second leading cause of death in the world. It is becoming increasingly clear that diet and lifestyle play a significant role in the development and progression of cancer. Thus, various dietary combinations can be proposed to reduce the risk of cancer and to improve the impact of basic therapy. Nutrition is closely linked to cancer. Food carcinogens, macronutrients, micronutrients such as vitamins A, C and D, dietary fiber, modulation of metabolism by diet, dietary supplements and anticancer agents in food affect the development of cancer. This article discusses research on the relationship between nutrition and cancer, as well as current dietary guidelines for reducing the risk of cancer. The aim of the study is to analyze information from the professional literature on the influence of various nutritional regimes in cancer patients. Conclusions. Proper nutrition can prevent the risk of cancer and improve the impact of treatment on the disease. Ketogenic diet is useful in combination with standard therapy on the basis of its ability to enhance the antitumor effects of classical chemotherapy and radiation therapy, its overall good safety and tolerability, as well as improving the quality of life. Mediterranean diet is a protective factor against cancer, due to the antioxidant and anti-inflammatory properties of the ingredients. Fasting is also a potentially effective strategy for inducing the differential stress resistance of cancer and normal cells as an adjunct to standard treatment. Promising benefits of vitamins in the prevention and treatment of cancer can be achieved through the use of new potent analogues, as well as combinations of vitamins in the early stages of cancer.